1981
DOI: 10.1029/ja086ia06p04471
|View full text |Cite
|
Sign up to set email alerts
|

Upstream hydromagnetic waves and their association with backstreaming ion populations: ISEE 1 and 2 observations

Abstract: Measurements from the Lepedea plasma instruments and the flux gate magnetometers on ISEE 1 and 2 are used to examine the nature of the hydromagnetic waves associated with the various classes of ions backstreaming from the earth's bow shock. The reflected ions, which are confined to a narrow energy and angular range, are accompanied by small amplitude (≲½γ peak to peak) left‐handed waves at frequencies close to 1 Hz in the spacecraft frame. Diffuse backstreaming particles with a broad energy spectrum are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
357
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 463 publications
(390 citation statements)
references
References 22 publications
32
357
1
Order By: Relevance
“…The waves in this interval are righthand polarized in the spacecraft frame (sr > 0). Knowing that the waves are propagating upstream in the plasma rest frame (since cp < 0) and that the hot beam low frequency modes have phase speeds much smaller than the solar wind speed, the sense of polarization in the spacecraft frame will be reversed to that in the plasma rest frame (Hoppe et al, 1981;Hoppe and Russell, 1983). We conclude that the waves in this region are left-hand polarized in the plasma rest frame, and can be identified as an Alfvén/left-hand resonant instability.…”
Section: Alfvén Mode Left-hand Resonant Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The waves in this interval are righthand polarized in the spacecraft frame (sr > 0). Knowing that the waves are propagating upstream in the plasma rest frame (since cp < 0) and that the hot beam low frequency modes have phase speeds much smaller than the solar wind speed, the sense of polarization in the spacecraft frame will be reversed to that in the plasma rest frame (Hoppe et al, 1981;Hoppe and Russell, 1983). We conclude that the waves in this region are left-hand polarized in the plasma rest frame, and can be identified as an Alfvén/left-hand resonant instability.…”
Section: Alfvén Mode Left-hand Resonant Instabilitymentioning
confidence: 99%
“…The study and identification of these distributions and magnetic signatures gives information about their interrelation and evolution (Fuselier, 1995;Killen et al, 1995) and is central to understand processes such as the thermalization of the solar wind (Greenstadt, 1985;Thomsen et al, 1990;Schwartz and Burgess, 1991;Dubouloz and Scholer, 1995), shock reformation (Burgess, 1989) and Fermi acceleration (Ellison, 1985;Giacalone et al, 1993) Numerous works have studied the plasma waves observed in the foreshock (Greenstadt et al, 1968;Fairfield 1969;Hoppe et al, 1981;Hoppe and Russell, 1983;Russell et al, 1987;Le, 1991; see special issue of J. Geophys. Res, vol 86, (A6) 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the variance analysis technique, including error estimates, has been given recently by Sonnerup and Scheible [1998]. A variety of different error estimates have appeared in the literature [Sonnerup, 1971;Lepping and Behannon, 1980;Hoppe et al, 1981;Kawano and Higuchi, 1995], but a complete analytical treatment is lacking. The present paper addresses the issue of statistical uncertaintie• when MVA is applied to actual experimental data, starting from first principles and employing the analytical approach.…”
Section: Introductionmentioning
confidence: 99%
“…WWs have been observed in nearly every space plasma environment including, but not limited to, the terrestrial magnetosphere [e.g., Russell et al, 1969], in the solar wind [e.g., Coroniti et al, 1982], upstream of IP shocks [e.g., Russell et al, 1983;Wilson III et al, 2009], downstream of IP shocks [Moullard et al, 1998[Moullard et al, , 2001], upstream of planetary bow shocks [e.g., Hoppe et al, 1981], and in the ramp of supercritical IP shocks [Wilson III et al, 2012].…”
Section: Introductionmentioning
confidence: 99%